The impact of an aged care pharmacist in a department of emergency medicine - Mortimer, C.; Emmerton, Lynne; Lum, E. (Wiley-Blackwell Publishing Ltd., 2011)
Rationale, aims and objectives: Departments of Emergency Medicine (DEM) have experienced increased demand largely because of the aging population. This project aimed to assess the impact of a specialist aged care pharmacist (ACP) on the efficiency and effectiveness of care of older patients seeking emergency treatment. Method: Eligible patients presenting to the DEM of Bundaberg Hospital (Australia), aged ≥65 years with a chronic condition, or ≥70 years without a chronic condition, and an Australian Triage Category score of ≥2, were alternately allocated to either the ACP (for medication reconciliation and medication review roles, along with patient education and referrals where warranted), or continued management by the DEM doctor (control group). Results: A total of 199 patients were included (intervention, n = 101; control, n = 98), with no significant difference in mean age or gender distribution. While the ACP-managed group demonstrated a significantly greater length of stay than the control group, some confounding was likely. The ACP demonstrated greater vigilance than usual care in ensuring completeness and accuracy in charted medication orders. The ACP also provided timely clinical review for medication-related problems, with 81 issues identified for 73 admitted patients, and 24 issues among the 28 discharged patients. Qualitative data were strongly supportive, valuing and accepting of the ACP role. Conclusions: This study provides evidence, on balance, supporting the integration of an ACP in the DEM assessing elderly patients. Further research of this role using longer sampling, in multiple sites and with economic analysis is recommended.